Comparison of Product Quality, Location, and Promotion of Kopi Kenangan and Leton Coffee Among Millennials and Generation Z in Pekanbaru City - Putri Diolanda, Elora; Berampu, Lailan Tawila; Wildah, Sri Wahyuni; Noviasari, Henni (Economics, Business and Management Science Journal, 2026)
This study aims to compare consumer perceptions of product quality, location, and promotion between Kopi Kenangan as a domestic brand and Leton Coffee as a local brand in Pekanbaru city. This study uses a quantitative approach. The population in this study consists of Kopi Kenangan and Leton Coffee consumers from the Millennial and Generation Z generations in Pekanbaru City. The sampling technique was obtained by distributing questionnaires to 100 respondents, then analyzed using descriptive analysis, data quality testing, normality testing, and Paired Sample T-Test with the help of SPSS software. The results show that there is no significant difference between the product quality of Kopi Kenangan and Leton Coffee among Millennials, but there is a significant difference between the product quality of Kopi Kenangan and Leton Coffee among Generation Z. Furthermore, there is a significant difference between the locations of Kopi Kenangan and Leton Coffee among Millennials and Generation Z. However, there was no significant difference between the promotion of Kopi Kenangan and Leton Coffee among Millennials and Generation Z